FLOOD RISK INDEX MAPPING OF AN AREA DOWNSTREAM OF A DAM IN CASE OF A BREAK - Alves Junior, Francisco Moreira; Kobiyama, Masato; Corseuil, Cláudia Weber (Mercator; Vol 22 (2023), 2023)
We aimed to evaluate the flood risk index due to the hypothetical break of the São Bento dam (SC, Brazil). The risk index was obtained by combining the hazard and vulnerability indices. The hazard index was obtained by multiplying the velocity by the depth of the water, simulated with HEC-RAS 2D. The simulated flood extent was 64.8 km2, with a maximum flow of 3586.60 m3·s-1, a depth of up to 2.0 m, and a velocity of up to 2.0 m·s-1 in most of the area. The formation of the breach occurred in 2.85 h, and the peak flow occurred at 1.67 h. The volume that overflowed with the break was 44.75 hm3. The flood wave reached 22.0 km in length, where the municipality of Forquilhinha is located. The risk index map showed that the risk is high up to 6 km from the dam since most people were at least 60 years old and had low incomes. In this location, the people were not safe inside buildings because they had a high probability of being destroyed. Thus, risk mapping may be adopted as a preventive measure to assist in preparing an emergency action plan and serve for environmental education and territorial planning. Keywords : Dam Break; HEC-RAS 2D; Risk Mapping.